Kui Hign Kui - Embalse para la acuicultura sostenible (2020)
The proposal starts from a macro design at the regional level that consists of the connection of the department with the center of the country, strengthening the infrastructure, improving the social and cultural part, protecting environmental wealth and, above all, promoting productive borders. Within the regional macro design, in the municipality of Calamar Guaviare, a plan of union of the urban area is designed with the site most affected by the eradication of illicit crops, in this there are the solutions to the aforementioned problems. The world above is divided into 2 worlds and the world below from within the world above is designed for sustainable infrastructure and sustainable economy projects, within the world below are social and environmental projects. The reservoir for sustainable aquaculture is a project that, within the proposed social reconstruction, covers education, work and food security issues, which mainly dignifies the lives of people affected by the armed conflict.